The Species of Rice Bug (Leptocorisa oratorius Fabricius) Egg Parasitoids in Rice Field in West Sumatera, Indonesia - Fri Maulina; Novri Nelly; Hidrayani Hidrayani; Hasmiandy Hamid (Jurnal Ilmu dan Teknologi Terapan Pertanian, 2020)
The species of egg parasitoid in rice bug is necessary to know to be used as biological agent in the field. The research aimed to determine spesies of parasitoid, diversity index, parasitization level and parasitoid mortality which found in rice bug eggs in rice fields in West Sumatra. Purposive random sampling was used in this research for determining the sampling locations. Collecting eggs sampling was conducted for 1 km along transect line in sampling location. The collected eggs of 12 sampling locations then observed and identified in Laboratory of Insect Bioecology, Faculty of Agriculture, Andalas University. The result showed that the kind of egg parasitoid found in the field were Hadronotus leptocorisae and Ooencyrtus malayensis with each parasitization level were 22.3 ± 11.1 % and 4.2 ± 5.3 %, each the mortality were 57.8 ± 26.4% and 30.6 ± 37%, the diversity of egg parasitoid was low with the index 0.3858 Based on Shannon-Wienner.